Approach to value stream mapping for make-to-order manufacturing - Mudgal, Devanshu; Pagone, Emanuele; Salonitis, Konstantinos (Elsevier, 2020)
This paper presents a new approach to the Value Stream Mapping (VSM), a proven tool of Lean Manufacturing (LM) in a Make-To-Order (MTO) manufacturing environment. The use of VSM in mass production has proven to be successful due to the predictable volume and repetitive product type. Within a MTO environment the product is tailored to specific requirements and varying volumes make it hard to balance production causing lean waste. The approach combines the classic VSM technique with commonality analysis to get a better understanding of the processes. Author illustrates this approach using a case study. Using VSM for MTO requires some changes to capture the attributes of product families required at different frequencies and volumes successfully
Keywords: Lean Production; Small and Medium Enterprises; Commonality; Product Family; Value Stream Mapping; Make-To-Order